The CRB commodity yearbook 2007 (Wiley, 2007)
Since 1939, professional traders, commercial hedgers, portfolio managers, and speculators have come to regard The CRB Commodity Yearbook as the "bible" of the industry. Here is a wealth of authoritative data, gathered from government reports, private industry, and trade and industry associations, all compiled by the Commodity Research Bureau, the organization of record for the entire commodity industry. The Yearbook is absolutely essential for identifying changing trends in supply and demand and for projecting important price movements. It gives investors: Worldwide supply/demand and production/consumption data for all the basic commodities and futures markets-from A(luminum) to Z(inc), including all the major markets in interest rates, currencies, energy, and stock index futures. Over 900 tables, graphs, and price charts of historical data, many of which show price history dating back to 1900,...